Faktor-faktor yang Memengaruhi Minat Mahasiswa Mengikuti Program Sinergi (S1-S2) Sekolah Pascasarjana IPB - Hariyadi, Effi; Cahyadi, Eko Ruddy; Slamet, Alim Setiawan (School of Business, Bogor Agricultural University (SB-IPB), 2022)
This study aims to analyze the interest of undergraduate students in the Synergy Program of the Graduate School of IPB (SPs IPB) based on the Theory of Planned Behavior (TPB). This study uses a sampling technique with a non-probability sampling method involving 389 active undergraduate student respondents with several parameters distributed through an online questionnaire. The data was then processed by analysis of the Structural Equation Modeling- Partial Square Least (SEM-PLS) using Smart PLS version 3 with reflective indicator measurements. The results of the research based on the TPB theory showed that all the variables in the TPB, namely the attitude variable, subjective norm and perception of control had a significant effect on increasing respondents' interest in participating in the SPs IPB synergy program. Furthermore, the results of the SEM-PLS analysis show that of the three TPB variables, the subjective norm variable has the highest influence on student interest compared to other variables. The subjective norm variable in this study was formed from several external factors, namely the dimensions of parents, dimensions of lecturers and dimensions of students. Thus, SPs IPB can increase the input of the synergy program participants by optimizing the three TPB variables, especially from the subjective norm variable through the role of parents in the form of providing information, fellow students in the form of delivering word of mouth information and lecturers in the form of providing recommendations. Keywords: intention, sinergy program SPs, sem pls, theory of planned behavior